(untitled) (Research, Society and Development, 2020)
The change in the paradigms of contemporary society leads us to rethink both the educational practices offered to students and the preparation of teachers for the responsible confrontation of current demands. In this sense, the present study aims to analyze the application of the concept of Lifelong Learning as a teaching strategy learning teacher education. The methodology is qualitative based on the literature review and the case study of the creation and application of the Digital Business discipline in the undergraduate environment. Combining theory with the results analyzed, it can be concluded that Lifelong Learning is of great relevance in the teaching-learning process and, increasingly, there is a need to rethink the practice and training of teachers, personal and professional, projecting important changes in these structures.